A 1D anionic lanthanide coordination polymer as an adsorbent material for the selective uptake of cationic dyes from aqueous solutions1. Issue 30 (14th August 2015) - Du, Pei-Yao; Li, Hui; Fu, Xin; Gu, Wen; Liu, Xin
<x xml:space="preserve">Abstract</x> A 1D anionic lanthanide complex has been prepared that can serve as a potential functional material to selectively remove cationic dyes from wastewater, especially methylene blue.